AMBIGUITY IN INTERCULTURAL COMMUNICATION: A CASE STUDY ON LANGUAGE AND CULTURAL DIFFERENCES - Jerico Devaly Damanik; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Semantic ambiguity constitutes a fundamental impediment in intercultural communication, especially where language and cultural divergences intersect in workplace settings. This qualitative case study examines how Indonesian migrant workers in Taiwan and their Taiwanese employers navigate communication challenges arising from linguistic, pragmatic, and cultural ambiguities. Data from interviews, observations, and document analyses reveal that phonological confusions, dialectal variations, indirect speech acts, and divergent cultural norms engender persistent misunderstandings. Findings highlight the need for comprehensive intercultural competence training incorporating linguistic nuances and pragmatic cultural awareness to mitigate ambiguity, improve communication effectiveness, and foster harmonious labor relations.